EDUCATION OF THE YOUNG GENERATION IN THE SPIRIT OF PATRIOTISM THROUGH MEMORIAL OF THE VICTIMS OF REPRESSION IN SCHOOLS OF UZBEKISTAN (Web of Teachers: Inderscience Research, 2026)
This scientific article has political and practical significance and is intended for all intellectuals who carry out spiritual propaganda work in schools. It helps to develop national values and implement new knowledge in the family, neighborhood, and secondary schools, in the meaningful organization of history, education, literature, and music lessons, and in conducting spiritual and educational events.